Technical and economic potential for photovoltaic systems on buildings - Fath, Karoline (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2018)
Finite fossil resources require the exploitation of alternative energy sources like photovoltaics. A methodology for the economic potential assessment of photovoltaic installations on buildings including building facades has been developed. It is based on detailed irradiation simulations and a combination of geographically referenced and statistical data and has been applied to the German building stock for 2015. A prognosis for the potential development until 2050 is given.